Analisis Hipertensi Sebagai Faktor Risiko Terjadinya Penyakit Ginjal Kronik - Satria Adi Nugraha; Sutarto; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2022)
Chronic kidney disease (CKD) is a disease that has a fairly high impact on morbidity and mortality in the community. The prevalence of CKD in the world reaches 8-16%, while in Indonesia according to basic health research data in 2018 at the age of 15 years the incidence of CKD is 0.64% and is increasing every year. Hypertension is one of the risk factors for CKD. Hypertension is the most common cardiovascular disease suffered by the community and according to WHO data in 2015 there were 1.13 billion people experiencing hypertension. The method used by the author in compiling this article is in the form of a literature review study covering the activities of collecting scientific sources both nationally and internationally and presenting a summary in the form of the most relevant publications. Hypertension has a relationship with the incidence of CKD. This is reinforced and in line with several studies that have been carried out and obtained the results that there is a significant relationship between hypertension and CKD.